PERAN PERCEIVED VALUE MEMEDIASI PENGARUH SERVICE QUALITY TERHADAP CUSTOMER LOYALTY PADA PELANGGAN AKASA KINTAMANI COFFEE - Yarsini, Ni Wayan; Suparna, Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.11.TAHUN.2023DO - 10.24843/EEB.2023.v12.i11.p18, 2023)
Currently the coffee business is predicted to be a business that will continue to grow in the future, and the amount of coffee consumption is predicted to continue to increase. In 2018 the increase in coffee consumption increased by 8%-10%, and in 2021 the coffee business is predicted to increase by 15%-20%. This study aims to determine the effect of service quality, perceived value and customer loyalty of Akasa Kintamani Coffee's. This study uses an associative quantitative approach. This research was conducted at Akasa Kintamani Coffee in Kintamani Bangli. The population in this study were all customers who came to Akasa Kintamani Coffee who had visited and bought products or food at Akasa Kintamani Coffee. The number of samples from the study was 65 people. Analysis techniques with SEM-PLS. The results showed that 1) Service quality had a significant positive effect on customer loyalty at Akasa Kintamani Coffee, 2) Service quality had a significant positive effect on perceived value at Akasa Kintamani Coffee, 3) Perceived value had a significant positive effect on customer loyalty at Akasa Kintamani Coffee, 4) Perceived value partially mediates the effect of service quality on customer loyalty at Akasa Kintamani Coffee.